Alteration in microbial community and antibiotic resistance genes mediated by microplastics during wastewater ultraviolet disinfection - Yang, Zeyuan; Liu, Peng; Wei, Haoyu; Li, Huang; Li, Jianlong; Qiu, Xinran; Ding, Rui; Guo, Xuetao (The Science of the total environment, 2022)
Microplastics (MPs) could be as a vector to colonize microorganisms and antibiotic resistance gene (ARGs) in surface water. However, little information is known regarding their changes by the presence of MPs in wastewater treatment. Here, the effects of different concentrations and sizes of polystyrene microplastics (PSMPs) on the distribution and removal of microbial communities and ARGs under ultraviolet disinfection of urban sewage have been systematically studied. Results showed that the presence of MPs altered abundance and functions of microorganisms in wastewater, despite different effects on different types of microorganisms. The most abundant ARGs in original disinfection tank sewage was rpoB2 (6.34%). A certain concentration range of MPs can improve the ability of specific types of ARGs in the UV disinfection process. Compared to the system without PSMPs, the content of Deinococcus-Thermus and Bacteroidetes phylum increased, while Actinobacteria and Proteobacteria phylum decreased in the presence of MPs. The microbial functions, especially the genetic information processing and metabolism were altered by the presence of PSMPs. In addition, PSMPs altered the content of ARGs, where the contents of OXA-182 and ErmH were increased, while adeF and ANT3-Iic were decreased. PSMPs also decreased the free ARB content in wastewater by providing colonization sites. The UV disinfection efficiency of microorganisms and ARGs was also intervened by PSMPs since they provided colonization sites and increased the water turbidity. The findings indicated that PSMPs altered the distribution and removal of microbial community and ARGs in ultraviolet disinfection of wastewater, highlighting the combined risks. [Display omitted] •PSMPs affected the distribution of microorganism and ARGs in UV disinfection.•MPs significantly increased the microbial functional genes.•The presence of MPs increased the survival of ARGs during UV irradiation.•MPs will hinder ultraviolet irradiation to remove microorganisms and ARGs.